Mirabegron improves quality-of-life, treatment satisfaction, and persistence in patients with overactive bladder: a multi-center, non-interventional, real-world, 12-month study. (4th May 2018) - Freeman, Robert; Foley, Steve; Rosa Arias, José; Vicente, Eduardo; Grill, Robert; Kachlirova, Zuzana; Stari, Anny; Huang, Moses; Choudhury, Nurul
Abstract: Objective: Observational studies can provide evidence about patient outcomes in routine clinical practice. This prospective, non-interventional study (BELIEVE) is the largest real-world European study to date to assess quality-of-life, treatment satisfaction, resource utilization, and persistence in patients with overactive bladder (OAB) who were prescribed mirabegron as part of routine clinical practice. Methods: The primary objective was to evaluate change from baseline in quality-of-life based on overactive bladder questionnaire (OAB-q) sub-scales. Secondary objectives included evaluation of treatment persistence, patient satisfaction, healthcare resource utilization and adverse events (AEs). Follow-up was for 12 months with visit windows at 2–4 and 10–12 months. Median change from baseline in total OAB-q and its sub-scales (Health-related quality-of-life [HRQoL] and symptom bother scale) were assessed. Results: Overall, 862 patients were enrolled from eight European countries. In the Full Analysis Set (FAS), 73.7% were female, mean age was 61.2 years; 47.7% ≥65 years. At baseline, 41.3% had switched from other OAB treatments, 42.2% were treatment naïve, 10.1% were lapsed, and 6.4% were on combination treatment. Symptom bother and HRQoL total scores improved from baseline to 2–4 and 10–12 months. There was a notable improvement in dry rate, increasing from 34.9% at baseline to 43.7% at 10–12 months in the FAS, and a reduction in pad use. Persistence was high, with 53.8% of FAS patients remaining on mirabegron at 10–12 months. Overall, no unexpected safety issues were observed and AEs were consistent with the known safety profile of mirabegron. Conclusion: Patients receiving mirabegron in a real-world setting reported meaningful improvements in QoL and health status, with a persistence rate of 53.8% at 12 months for the FAS. No unexpected safety issues were observed, and AEs were consistent with the known safety profile of mirabegron.